Theme issue: Design as a social process. (2002) - Bucciarelli, L. L.
In our call for submissions to this special edition of the Journal of Design Research on the theme "Design as a Social Process" we left it quite open as to the meaning of "social" though we did try to narrow the field by suggesting authors focus on how social values and norms effect choices and so ultimately the form and functioning of the product. Still, the range of subject matter displayed in the submissions was much wider than we anticipated. Maintaining our focus proved difficult indeed.